A Need for Tailored Programs and Policies to Reduce Rates of Alcohol-related Crimes for Vulnerable Communities and Young People: An Analysis of Routinely Collected Police Data. (26th May 2018) - Snijder, Mieke; Calabria, Bianca; Dobbins, Timothy; Knight, Alice; Shakeshaft, Anthony
Abstract : This study analysed routinely collected police data in New South Wales, Australia, to identify individual and community characteristics associated with alcohol-related crimes. Young people, Aboriginal Australians, socio-economically disadvantaged communities, remote and regional communities and communities with higher per capita rate of on-venue liquor licenses are at risk of alcohol-related crimes. Abstract: Background and aims: Given ongoing community concern about high rates of alcohol-related crimes (ARCs) experienced by disadvantaged populations, a more specific and nuanced understanding of factors associated with ARCs would help inform the development of more sophisticated programs and policies aimed at reducing ARCs. This study estimates rates of ARCs across all communities in New South Wales (NSW), Australia, using routinely collected police data; investigates whether there are differences between communities; and identifies individual and community characteristics that are significantly associated with higher rates of ARCs. Short summary: This study analysed routinely collected police data in New South Wales, Australia, to identify individual and community characteristics associated with alcohol-related crimes. Young people, Aboriginal Australians, socio-economically disadvantaged communities, remote and regional communities and communities with higher per capita rate of on-venue liquor licenses are at risk of alcohol-related crimes. Methods: Age standardized rates of ARCs were calculated. A multi-level Poisson regression analysis was conducted to investigate the individual and community factors that were statistically significantly associated with higher rates of ARC, separately for Aboriginal and non-Aboriginal Australians. Results: Rates of ARCs were statistically significantly higher for Aboriginal Australians, young people (aged 13–37 years) and on weekends. ARCs varied significantly across communities, and were significantly higher in remote or regional communities, in communities with a higher per capita rate of on-venue licences, and for socio-economically disadvantaged communities for non-Aboriginal Australians, but not for Aboriginal females. Conclusion: This analysis shows that the impact of national-level and jurisdictional-level legislation and policies is uneven across communities and defined populations, leaving young people, socio-economically disadvantaged communities and Aboriginal Australians at increased risk of ARCs. To more equitably reduce the exposure of all Australians to ARC, mechanisms that effectively engage vulnerable communities and defined populations, need to be developed in consultation with them, implemented and evaluated.